Analisis Kinerja Pegawai pada Dinas Komunikasi Dan Informatika Kabupaten Karawang - Robby Darmawan; Uus Mohammad Darul Fadli (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this analysis is to evaluate the performance of Karawang district communications and information services employees. This analysis focuses on the extent to which employees can carry out and complete tasks effectively and efficiently. Research methodology This will analyze questionnaire data using descriptive statistical techniques given to each employee of the Karawang Regency Communication and Information Service. It is hoped that the results can become recommendations for improving employee performance and public services at the Karawang Regency Communication and Information Service.